KONTRIBUSI KETERAMPILAN MEMBACA APRESIATIF TEKS CERITA FABEL TERHADAP KETERAMPILAN MEREPRODUKSI TEKS CERITA FABEL SISWA KELAS VIII SMPN 12 PADANG - Nusri, Nadiatul; Basri, Irfani (Universitas Negeri Padang, 2019)
ABSTRACT This article has written the contribution of appreciative reading skill of fable story text to the skills of producing fable story texts at students VIII class of SMPN 12 Padang. This research is quantitative research using the descriptive method and the contribution research design. The research data is the test result score of appreciative reading skill of fable story text and the test result score of reproducing fable story text. The data has obtained through two types of test that are the objective test which uses reproducing fable story text . Based on the result of data analysis and the discussion, the researcher concludes the three things follow; first, the average score of the student’ reading appreciative reading skill of fable story text at students VIII class of SMPN 12 Padang is in the good qualification (82.01). Second, the average score of the student’ reproducing fable story text students at VIII class of SMPN 12 Padang is in the good qualification (79,17). Third, there are the significant contributions between the appreciative reading skill of fable story text toward the students reproducing fable story text students at VIII class of SMPN 12 padang as much as 84,82%. Kata kunci: Kontribusi, Keterampilan, Membaca Apresiatif, Mereproduksi, Teks Cerita Fabel